Skid Resistance Measuring Techniques Using Portable Testing Tools for Road Application - Mazlan, Rafidah; Mohd Lazi, Mohd Khairul Afzan; Mohd Jakarni, Fauzan; Kamarudin, Siti Nur Naqibah; Shahrin, Muhammad Irfan; Zolkepli, Muhammad Farhan; Hassan, Sitti Asmah; Mohd Warid, Muhammad Naqiuddin (Recent Trends in Civil Engineering and Built Environment, 2025)
Pavement skid resistance is another highway element that has a direct impact on driving safety. Adequate pavement skid resistance is a key requirement for safe road operations. Poor safety pavement happened due to less friction between vehicle tyres and pavement that cause problems for driver to control vehicle in proper movement and direction. The conventional measurement and prediction of the skid resistance apparatus is a highly challenging due to rapid development that. Thus, this article elaborated on state-of-art of the recent progress of testing apparatuses and evaluation techniques concerning for skid resistance was illustrated in detail in term of mechanism, measurement, methods and application. Measurement techniques of skid resistance in situ such as. The current advances for skid resistance of asphalt pavement from recognized research works are summarized. This manuscript recommends a few key research directions such as the gap between current and conventional portable apparatus of skid resistance should be linked to identify more precise approximation of frictional pavement properties in the phase of testing. Besides that, the article established standard testing procedures for measurement of microtexture and macrotexture of asphalt pavement.